Prevalencia de Mastitis y caracterización productiva en pequeños productores de Tenjo y Simijaca, Cundinamarca, Colombia. - Prieto Moreno, Angie Natalia; Hurtado Prieto, Diana Catalina (Universidad Antonio Nariño, 2022)
Mastitis is a disease caused by microorganisms that invade the udder producing a mild or severe inflammatory process generating changes in the tissue glandular and milk, man is a factor that directly influences the presentation because he is the one who gives the management to the machines and animals, keeping an order and a proper milking routine. The objective of this study was to determine the prevalence of mastitis and characterize some productive parameters of small milk producers in Tenjo and Simijaca (Cundinamarca), to answer this objective, two articles, the first a scientometric analysis on different studies of mastitis in Colombia and the second characterizing and determining the prevalence in small producers